Perancangan Pembangkit Listrik Tenaga Surya (PLTS) Off Grid 500 Watt di Dusun Baku Desa Sumi Kecamatan Lambu: Penelitian - M. Ziaul Fikar; Sofyan Winardin (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Electricity access in remote areas such as Dusun Baku, Desa Sumi, Kecamatan Lambu, remains a significant challenge due to the absence of PLN (state electricity company) grid infrastructure. This study aims to design a 500-watt Off-Grid Solar Power Plant (Photovoltaic/PLTS) system as a sustainable and environmentally friendly energy solution. The research uses an experimental approach, beginning with literature review, field data collection, and energy requirement analysis. The designed system consists of two 250 Wp solar panels, an MPPT-type solar charge controller, a 12V 200Ah VRLA battery, and a 1000W pure sine wave inverter. The system is capable of producing approximately 1.875 kWh per day, sufficient to meet basic household electricity needs such as lighting, fan, television, and mobile device charging. This Off-Grid PLTS provides a practical, cost-effective, and sustainable electricity solution for underserved areas while supporting Indonesia’s national renewable energy target.